2015
DOI: 10.1002/pc.23871
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of microscopic characteristic influences on the mechanical properties of polymer‐matrix composites

Abstract: In this study, an isoparametric micro‐mechanical model is developed to study the failure behaviors under biaxial loadings for composites with different fiber arrangements. For validating the method, the numerical results of the unidirectional (UD) composite lamina with consideration of two different failure criteria (the constituent failure criterion and UD failure criterion) are compared with the experimental results. On this basis, the fiber arrangements and fiber off‐axis angles influence on the failure env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In 2D FE simulations of metal matrix composites with nonhardening matrix, it was found that for low fiber volume fractions (b0.4), hexagonal and square array gave similar strengths [40]. However for higher volume fractions (N0.4), the strength of the square array was much higher than hexagonal [41,42], and increased with increase in fiber volume fraction [42]. In comparison, results of the present study indicate that hexagonal, square and random arrays have similar strengths.…”
Section: -D Simulation Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In 2D FE simulations of metal matrix composites with nonhardening matrix, it was found that for low fiber volume fractions (b0.4), hexagonal and square array gave similar strengths [40]. However for higher volume fractions (N0.4), the strength of the square array was much higher than hexagonal [41,42], and increased with increase in fiber volume fraction [42]. In comparison, results of the present study indicate that hexagonal, square and random arrays have similar strengths.…”
Section: -D Simulation Resultsmentioning
confidence: 89%
“…A few studies have been conducted on the influence of volume fraction on the mechanical properties of different structural arrangements [40][41][42]. In 2D FE simulations of metal matrix composites with nonhardening matrix, it was found that for low fiber volume fractions (b0.4), hexagonal and square array gave similar strengths [40].…”
Section: -D Simulation Resultsmentioning
confidence: 96%
“…Moreover, two periodic arrangements, that is square edge packing and square diagonal packing (as shown in Ref. ), are considered. The results of the longitudinal thermal conductivity coefficient k 11 and transversal thermal conductivity coefficients k 22 or k 33 for AS4/3501–6 composites with respect to temperature variations are shown in Fig.…”
Section: Model Validationmentioning
confidence: 99%
“…In recent years, composites, which are considered to be the attractive materials due to their high strength and stiffness, have been widely used in aerospace fields . Loading and environment variation effect on composites will lead to material aging, fatigue and crack, which may give rise to the failure of composite structures .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [7][8] and theoretical methods [9][10] have been used to investigate the mechanical features and damage mechanisms of composite blades. However, for a heterogeneous material, it is difficult to reveal the intrinsic relations between its macroscopic and microscopic characteristics, such as fiber arrangements and fiber shape [11][12][13][14], by experimental methods. As a result, more and more researchers are using numerical methods to study their mechanical properties and optimally design composite wind turbine blades.…”
Section: Introductionmentioning
confidence: 99%